Passive heating-induced changes in muscle contractile function are not further augmented by prolonged exposure in young males experiencing moderate thermal stress - Treigyte, Viktorija; Chaillou, Thomas; Eimantas, Nerijus; Venckunas, Tomas; Brazaitis, Marius (Frontiers in Physiology, 2024)
Background: We investigated the impact of 1) passive heating (PH) induced by single and intermittent/prolonged hot-water immersion (HWI) and 2) the duration of PH, on muscle contractile function under the unfatigued state, and during the development of muscle fatigue. Methods: Twelve young males volunteered for this study consisting of two phases: single phase (SP) followed by intermittent/prolonged phase (IPP), with both phases including two conditions (i.e., four trials in total) performed randomly: control passive sitting (CON) and HWI (44-45 oC; water up to the waist level). SP-HWI included one continuous 45-min bath (from 15 to 60 min). IPP-HWI included an initial 45-min bath (from 15 to 60 min) followed by eight additional 15-min baths interspaced with 15-min breaks at room temperature between 75 and 300 min. Intramuscular (Tmu; measured in the vastus lateralis muscle) and rectal (Trec) temperatures were determined. Neuromuscular testing (performed in the knee extensors and flexors) was performed at baseline and 60 min later during SP, and at baseline, 60, 90, 150 and 300 min after baseline during IPP. A fatiguing protocol (100 electrical stimulations of the knee extensors) was performed after the last neuromuscular testing of each trial. Results: HWI increased Tmu and Trec to 38-38.5 °C (P<0.05) during both SP and IPP. Under the unfatigued state, HWI did not affect electrically induced torques at 20 Hz (P20) and 100 Hz (P100). However, it induced a shift towards a faster contractile profile during both SP and IPP, as evidenced by a decreased P20/P100 ratio (P<0.05) and an improved muscle relaxation (i.e., reduced half-relaxation time and increased rate of torque relaxation; P<0.05). Despite a reduced voluntary activation (i.e., -2.63 ± 4.19 % after SP-HWI and -5.73 ± 4.31 % after IPP-HWI; condition effect: P<0.001), HWI did not impair maximal isokinetic and isometric contraction torques. During the fatiguing protocol, fatigue index and the changes in muscle contractile properties were larger after HWI than CON conditions (P<0.05). Finally, none of these parameters were significantly affected by the heating duration. Conclusion: PH induces changes in muscle contractile function which are not augmented by prolonged exposure when thermal stress is moderate.